2011
DOI: 10.1097/gco.0b013e32834ab544
|View full text |Cite
|
Sign up to set email alerts
|

Genital trauma in prepubertal girls and adolescents

Abstract: Genital injuries whether accidental or intentional need to be reported with standardized terminology to allow for comparisons between reported outcomes. Motor vehicle accidents associated with pelvic fractures may result in bladder or urethral trauma. Adverse long-term psychosocial behaviors may be sequelae of child sexual abuse. FGM is willful damage to healthy organs for nontherapeutic reasons, and a form of violence against girls and women. Healthcare providers should counsel women suffering from the conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In comparison to the literature on pediatric female genital trauma, in which several reviews exist to guide the clinician, 9 there is a paucity of literature on general pediatric male genital trauma with the majority focusing on specific injuries, such as toilet seat injury, 1 penile zipper entrapment, 10 and animal bites. 11 However, a recent retrospective review of 74 boys with nonsexual genital trauma seen at a single institution demonstrated that toddlers were most commonly affected by falls or injuries related to toilet seats; school-aged children by kicks, falls, or sports-related injuries; and adolescents by motorcycle accident-related injuries.…”
Section: Commentmentioning
confidence: 99%
“…In comparison to the literature on pediatric female genital trauma, in which several reviews exist to guide the clinician, 9 there is a paucity of literature on general pediatric male genital trauma with the majority focusing on specific injuries, such as toilet seat injury, 1 penile zipper entrapment, 10 and animal bites. 11 However, a recent retrospective review of 74 boys with nonsexual genital trauma seen at a single institution demonstrated that toddlers were most commonly affected by falls or injuries related to toilet seats; school-aged children by kicks, falls, or sports-related injuries; and adolescents by motorcycle accident-related injuries.…”
Section: Commentmentioning
confidence: 99%
“…The types of injuries seen include straddle, accidental penetrating and vaginal insufflation injuries leading to tears from sudden expansion during water slide falls. 43 By far the commonest injury presenting in more than 80% of cases is a straddle injury. These occur following a fall onto objects with the full force of the bodyweight, leading to compression of the soft tissues of the vulva between the flat surface of the object and the underlying bones of the pelvis.…”
Section: Accidental Vulval Trauma and Foreign Bodiesmentioning
confidence: 99%
“…These occur following a fall onto objects with the full force of the bodyweight, leading to compression of the soft tissues of the vulva between the flat surface of the object and the underlying bones of the pelvis. 7,43 Depending on the impact, lacerations and haematomas of the labia, clitoral fold and periurethral tissue can be seen. Accidental penetrating injuries occur if the child falls onto a sharp or pointed object; for example, a bath toy, fence post or the sharp edges of furniture.…”
Section: Accidental Vulval Trauma and Foreign Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Merritt [27] offers a comprehensive review of the important topic of genital trauma. She compares accidental and intentional genital trauma and addresses the cultural practice of female genital mutilation (FGM).…”
Section: Genital Trauma and Assaultmentioning
confidence: 99%